The Land Bleeds, the Culture Withers: Eco-Induced Cultural Crisis in Rudolf Anaya’s "Devil Deer" - Paudel, Narayan (Myagdi Guru, 2025)
The paper explores the issues of eco-critical warnings against environmental degradation that transgresses nature's carrying capacity, threatening both the physical landscape and the cultural fabric of Chicano communities as portrayed in Anaya's “Devil Deer.” Employing the duel frameworks of environmental justice and postcolonial ecocriticism - Rob Nixon's concept of "slow violence", this paper argues that Anaya masterfully depicts an eco-induced cultural crisis within the New Mexican Southwest. The paper aims to analyse how colonial-capitalist exploitation, embodied by the Los Alamos National Laboratory manifests through exclusionary practices and insidious contamination directly trigger the systematic unravelling of Chicano cultural identity, spirituality, traditional food-chain, and psychosocial cohesion. Through the analytical research design, the paper explores the animate land as a sacred repository, the Devil Deer as a monstrous symbol of slow violence and cultural corruption, and the protagonist Cruz's liminal struggle as the embodiment of this crisis. The findings reveal the inextricable link between ecological health and cultural survival demonstrating that when land suffers under exploitation and injustice, culture inevitably deteriorates. The study concludes by emphasizing the necessity of environmental protection for both physical and cultural survival, enriching scholarly discourse on ecocriticism and environmental justice.